Editorial introduction: Design issues and practical questions for demand-oriented seed systems - Almekinders, Conny J. M.; Mausch, Kai; Donovan, Jason (SAGE Publications, 2021)
This special issue is a collection of papers that brings together different views on and experiences with seed systems and reflects the breadth of perspectives within CGIAR and beyond. The contributions relate to the major challenges facing seed systems research and development in different contexts and for different crops. One point of agreement among these articles is the need for the development of varieties and the delivery of seeds to be more demand-orientated. This introduction reflects on the implications for CGIAR and affiliated breeding programmes which aim to accelerate varietal uptake and turnover and rely on more effective seed delivery. Here, we outline how the various contributions in this special issue relate to this agenda. We conclude that realism about which farming households can be served by current approaches to seed system development is needed and argue that a wider range of partnerships will be required to broaden the reach of seed systems.